A bio-based epoxy resin from rosin powder with improved mechanical performance. Issue 4 (29th September 2020) - Demircan, Gökhan; Kisa, Murat; Özen, Mustafa; Açikgöz, Abuzer; Aktaş, Bülent; Ali Kurt, Mehmet
Abstract : Today, with the increasing sensitivity to environmental issues, bio-based materials are needed as an alternative to traditional materials. Rosin is used for biomaterial production due to its abundance in nature and cheapness. This study aims to produce bio-epoxy using powdered rosin with enhanced mechanical properties. Powdered rosin was used at 1, 3 and 5 wt.% to study the effect of additive ratios. Three different mixing methods were used to make the mixture homogeneous. A magnetic stirrer was used in the first method, an ultrasonic stirrer was used in the second method and both were used in the third method. Bio-epoxy was successfully synthesized, and mechanical properties were examined by tensile, compression, density and hardness tests. As a result, it was determined that the best mixing method was the third mixing method, and the best results in additive ratios were obtained at 1 wt.% for tensile strength (5.63%) and hardness (14.41%) and at 5 wt.% for compression strength (8.28%).